2022
DOI: 10.1371/journal.pmed.1003858
|View full text |Cite
|
Sign up to set email alerts
|

The impact of removing financial incentives and/or audit and feedback on chlamydia testing in general practice: A cluster randomised controlled trial (ACCEPt-able)

Abstract: Background Financial incentives and audit/feedback are widely used in primary care to influence clinician behaviour and increase quality of care. While observational data suggest a decline in quality when these interventions are stopped, their removal has not been evaluated in a randomised controlled trial (RCT), to our knowledge. This trial aimed to determine whether chlamydia testing in general practice is sustained when financial incentives and/or audit/feedback are removed. Methods and findings We undert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Several studies have documented declines in quality of care after the withdrawal of financial incentives, 18 19 20 21 22 23 24 often back to levels similar to or worse than before the incentivisation. 18 19 20 22 24 However, other studies have observed no decline in quality of care, 13 14 15 16 17 although for one of these studies, care remained partially incentivised through other indicators for seven of the eight measures examined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have documented declines in quality of care after the withdrawal of financial incentives, 18 19 20 21 22 23 24 often back to levels similar to or worse than before the incentivisation. 18 19 20 22 24 However, other studies have observed no decline in quality of care, 13 14 15 16 17 although for one of these studies, care remained partially incentivised through other indicators for seven of the eight measures examined.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented declines in quality of care after the withdrawal of financial incentives, 18 19 20 21 22 23 24 often back to levels similar to or worse than before the incentivisation. 18 19 20 22 24 However, other studies have observed no decline in quality of care, 13 14 15 16 17 although for one of these studies, care remained partially incentivised through other indicators for seven of the eight measures examined. 16 Another study that followed-up a trial of incentives for diabetes care did not observe declines in quality when incentives were withdrawn, but the study also did not observe consistent improvements when incentives were introduced, making lack of change after withdrawal hard to interpret.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Credentialing RNs and AHPs aimed to create opportunities for STI testing in clinical encounters that did not involve a GP, whereas having pathology forms presigned by a GP allowed these tests to receive Medicare funding under the signing GP's provider number. Enhanced data reporting has been shown to be an important component of continuous quality improvement (CQI) systems implemented at ACCHSs [40,41]. These 3 components aimed to increase STI testing outside of the health assessment.…”
Section: The Systems Changementioning
confidence: 99%